(Re)Habitat. A reintegração da habitação na cidade consolidada. Berlim (1957,1984) Porto (1956,1974) - Marina de Castro Risto (2014)
The present thesis consists in a comparative study over the mutation/transformationof the attitudes and thoughts about the city, featuring paradigms'evolution of throughout the twentieth century. It's a period marked by modernistand post modernist influences, which come to reflect in the practicedurban policies and in the understanding of dwelling in its relation with thecity.Therefore, and taking the cities of Porto and Berlin as example, severalapproaches are put in confrontation, characterizing intervention practicesin a national and international context. By this mean, two paradigmaticcases are exposed which, despite having different contexts, share thesame problem of the city, in response to a common origin: the crisis anddwelling emergency. Within this theme, the pratical cases of the Interbauof Hansaviertel, BERLIM (1957) and Plano de Melhoramentos at PORTO(1956-1966) are approached, in contrast to the Operações S.A.A.L./Norte,PORTO (1974-1976) and the Internationale Bauausstellung (IBA) of BERLIMin the 80's, in a critical perspective to the model of modernist city aswell as representing an attempt to overcome the simplistic of the Modern'sFunctionalism.Thus, it is intended to encourage a reflection on the projectual methodin the context of consolidated city considering the form of dwelling in thecity, as an integral and generating part of it.